2005
DOI: 10.1002/adma.200401592
|View full text |Cite
|
Sign up to set email alerts
|

Optical Recording Materials Based on Photoisomerization of Guest Molecules of a Polymeric Crystalline Host Phase

Abstract: Optical recording technology has a major advantage over other recording technologies, namely, that reading and writing of data is accomplished by light, so that no physical contact between the media and the optical head occurs. The storage capacity of these optical media (e.g., disks) is limited by the size of the smallest marks on their surfaces that can be read by the wavelength of light used. In this communication, we present a possible data storage system with molecular-sized (» 200 3 ) marks that also g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 35 publications
(2 reference statements)
0
47
0
Order By: Relevance
“…On this basis, films presenting s-PS/active guest co-crystals have been proposed as advanced materials, mainly for optical applications (e.g. fluorescent, photo-reactive, chromophore and nonlinear optical materials) [57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, films presenting s-PS/active guest co-crystals have been proposed as advanced materials, mainly for optical applications (e.g. fluorescent, photo-reactive, chromophore and nonlinear optical materials) [57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that both NBD and QDC possess positional and orientational order with respect to the polymeric host crystallographic axes (20). It was demonstrated (20) that NBD can form stable clathrate and/or intercalate phases within s-PS films and that photoisomerization of NBD to QDC can be easily achieved in these films.…”
Section: Scheme 1 Photoinduced Isomerization Of Norbornadiene (Nbd) Imentioning
confidence: 99%
“…In some recent studies it has been reported that norbornadiene could form a clathrate phase with sPS and that efficient valence photoisomerization of N to Q in the crystalline phase can be achieved [30,31].…”
Section: Photoreactive Co-crystals: Optical Memoriesmentioning
confidence: 99%